KELAYAKAN USAHATANI TEBU DENGAN SISTEM TANAM JURING GANDA DI JAWA TIMUR DAN JAWA TENGAH - Lintje Hutahaean; Q Dadang Ernawanto (Jurnal Pengkajian dan Pengembangan Teknologi Pertanian, 2015)
ABSTRACT                The Feasibility of Sugar Cane Farming with Double Row Cropping System in East Java and Central Java. Technology innovation of double rows cropping system in sugar cane farming, as the so called “Juring Ganda” is a breaktrough by IAARD to improve the productivity aimed to support sugarcane self-sufficiency as well as to increase farmers’ income. This assessment aimed to analyze the financial feasibility of the double rows cropping system and to compare the differences of income between double and single cropping system. The research has been conducted in Central Java Province (Pati, Karang Anyar, Pekalongan, Klaten, Tegal Regency) and East Java Province (Pamekasan Regency) in 2013. Data were collected using survey to 15 farmers for each cropping system who were selected randomly. The types of data collected were: sugar cane farming characteristics (variety, cultivation, production, rendemen taxation, sugarcane prediction yield, etc); financing structures (cost for seedling, fertilizer, labours, sugar’s price), and structure of farmer’s income per hectare. Data were analyzed using losses and gains approach reflected by the marginal benefit cost ratio (MBCR), and using t test (t-student) for incomes differences. The results showed that: (a) the double row cropping system of sugar cane farming in the assessment locations was feasible, (b) additional costs of Rp 2.61 million per hectare in double rows cropping system led to additional revenue of Rp 4.67 million per hectare with MBCR value of 1.79, and (c) statistically, farmer’s income from double row system was significantly different from single row. Thus, it can be implied that double rows cropping system of sugarcane farming is an alterantive to be developed. Keywords: Sugarcane, double rows cropping, feasibility ABSTRAKTeknologi budidaya juring ganda pada tebu merupakan salah satu terobosan inovasi Balitbangtan untuk meningkatkan produktivitas tebu rakyat dalam upaya mendukung produksi gula nasional, sekaligus meningkatkan pendapatan petani tebu. Pengkajian yang bertujuan untuk menganalisis kelayakan finansial usahatani tebu sistem tanam juring ganda (JG) dan menguji perbedaan pendapatannya dibandingkan dengan sistem tanam juring tunggal (JT). Pengkajian telah dilakukan di Provinsi Jawa Tengah (Kabupaten Pati, Karang Anyar, Pekalongan, Klaten, Tegal) dan Provinsi Jawa Timur (Pamekasan) pada tahun 2013. Pengumpulan data dilakukan melalui survey menggunakan daftar pertanyaan terhadap 15 orang petani tebu sistem JG dan 15 orang petani tebu dengan sistem JT yang terpilih sebagai responden secara acak sederhana. Jenis data yang dikumpulkan utamanya meliputi karakteristik usahatani tebu (penggunaan varietas tebu, penggunaan pupuk, produksi, taksiran rendemen gula dan produksi gula per hektar), struktur pembiayaan (pembelian bibit, pupuk, upah kerja, harga gula), dan pendapatan usahatani tebu per hektar. Kelayakan usahatani tebu sistem tanam juring ganda dianalisis menggunakan “losses and gains” yang direfleksikan dalam marginal benefit cost ratio (MBCR), dan untuk menguji perbedaan pendapatan JG dengan JT digunakan uji beda dengan Uji t (t student). Hasil pengkajian menunjukkan bahwa: (a) Penerapan sistem tanam juring ganda pada usahatani tebu layak secara finansial, (b) Penambahan biaya sebesar Rp2,61 juta per hektar dapat menghasilkan tambahan pendapatan sebesar Rp4,67 juta per hektar, dengan nilai MBCR 1,79, dan (c) Pendapatan usahatani tebu sistem tanam juring tunggal tersebut terbukti berbeda nyata dibandingkan pendapatan petani tebu juring tunggal. Implikasinya, usahatani tebu sistem juring ganda dapat menjadi pilihan untuk dikembangkan. Kata kunci: Tebu, juring ganda, kelayakan